Facilitating the shift from tree planting to promoting community-based forest enterprises in the Philippines - Wardell, D.A. (World Agroforestry Centre, 2021)
This brief discusses the processes to facilitate a progressive shift in the current culture of the Department of Environment and Natural Resources’ Forest Management Bureau (DENR-FMB) from ‘tree planting, meeting planting targets and providing direct incentives such as tree seedlings’ to one that also recognizes the critical role of an ‘appropriate enabling environment to establish an overarching climate of enterprise in the Philippines. This will include greater recognition of the role of indirect incentives, the importance of smallholders’ tree and forest management, and fostering entrepreneurship and the marketing of timber and non-timber forest products (NTFPs) by smallholders. The recently adopted Forest Investment Road Map (FIRM), with the vision, ‘Revitalized Philippine Forestry Investment towards inclusive growth and sustainable development through local and foreign direct investment to increase the GDP contribution of the forest sector in the national economy’ is a welcome initiative by DENR-FMB to promote this transition (2019).1 Drawing on successful experience with decentralized environmental management and private-sector initiatives, this brief presents a tabulated summary of recommended activities to help restore investor confidence in the Philippines and the emergence of stronger and better-organized smallholders, as well as community-based forest enterprises (CBFEs) producing both timber and NTFPs